Flexible Wireless Receivers: On-Chip Testing Techniques and Design for Testability - Ramzan, Rashad (Linköpings universitet, Elektroniska komponenter, 2009)
In recent years the interest in the design of low cost multistandard mobile devices has gone from technical aspiration to the commercial reality. Usually, the emerging wireless applications prompt the conception of new wireless standards. The end user wants to access voice, data, and streaming media using a single wireless terminal. In RF perspective, these standards differ in frequency band, sensitivity, data rate, bandwidth, and modulation type. Therefore, a flexible multistandard radio receiver covering most of the cellular, WLAN, and short range communication standards in 800MHz to 6GHz band is highly desired. To keep the cost low, high level of integration becomes a necessity for the multistandard flexible radio. Due to aggressive CMOS scaling the fT of the transistors has surpassed the value of 200 GHz. Moreover, as the CMOS technology has proven to be the best suited for monolithic integration, therefore it seems to be the future choice for the physical implementation of such a flexible receiver. In this thesis, two multiband sampling radio receiver front-ends implemented in 130 nm and 90 nm CMOS including test circuitry (DfT) are presented that is one step ahead in this direction. In modern radio transceivers the estimated cost of testing is a significant portion of manufacturing cost and is escalating with every new generation of RF chips. In order to reduce the test cost it is important to identify the faulty circuits very early in the design flow, even before packaging. In this thesis, on-chip testing techniques to reduce the test time and cost are presented. For integrated RF transceivers the chip reconfiguration by loopback setup can be used. Variants including the bypassing technique to improve testability and to enable on-chip test when the direct loopback is not feasible are presented. A technique for boosting the testability by the elevated symbol error rate test (SER) is also presented. It achieves better sensitivity and shorter test time compared to the standard SER test. Practical DfT implementation is addressed by circuit level design of various test blocks such as a linear attenuator, stimulus generator, and RF detectors embedded in RF chips without notable performance penalty. The down side of CMOS scaling is the increase in parameter variability due to process variations and mismatch. Both the test circuitry (DfT) and the circuit under test (CUT) are affected by these variations. A new calibration scheme for the test circuitry to compensate this effect is presented. On-chip DC measurements supported by a statistical regression method are used for this purpose. Wideband low-reflection PCB transmission lines are needed to enable the functional RF testing using external signal generators for RF chips directly bonded on the PCB. Due to extremely small chip dimensions it is not possible to layout the transmission line without width discontinuity. A step change in the substrate thickness is utilized to cancel this effect thus resulting in the low-reflection transmission line. In summary, all of these techniques at the system and circuit level pave a way to new opportunities towards low-cost transceiver testing, especially in volume production.